2012
DOI: 10.1055/s-0032-1323157
|View full text |Cite
|
Sign up to set email alerts
|

Paranasal Sinus Involvement in Metastatic Carcinoma

Abstract: Metastatic carcinoma involving the paranasal sinuses is uncommon. One hundred-sixty seven cases have been published in the literature since 1951. Symptoms, signs, and rhinoscopic and imaging findings are often nonspecific, and the diagnosis may be missed for considerable time. Therefore, a high level of suspicion is warranted in patients with known malignancies presenting with persistent or recurrent rhinosinusitis or facial complaints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…The rectal adenocarcinoma metastases to paranasal sinuses are exceedingly rare, notably in the frontal sinus [2 , 3] . The spread of tumor cells can be hematogenous or meningeal [5] . The rectal venous plexus communicates with the azygos system via the middle rectal vein, the common iliac vein and the ascending lumbar vein [4] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The rectal adenocarcinoma metastases to paranasal sinuses are exceedingly rare, notably in the frontal sinus [2 , 3] . The spread of tumor cells can be hematogenous or meningeal [5] . The rectal venous plexus communicates with the azygos system via the middle rectal vein, the common iliac vein and the ascending lumbar vein [4] .…”
Section: Discussionmentioning
confidence: 99%
“…Those veins are without valves, and an increase of abdominal pressure can drive tumor cells into the vertebral venous plexus [4] , which has been postulated as a possible route for the hematogenous spread of cancer cells to the head and neck [2] , since it communicates with the great venous plexus of the head and the plexus of the paranasal sinuses. The meningeal spread if it is reached is possible [5] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other common metastases to the paranasal sinuses are breast, lung and prostate. 2 Only two cases have reported metastases from endometrial primaries to the paranasal sinuses. Scott et al 3 reported the first case of a stage 2A endometrioid-type endometrial adenocarcinoma spreading to the ethmoid sinus.…”
Section: Discussionmentioning
confidence: 99%